Rational Choice Meets the New Politics: Choosing the Scottish Parliament's Electoral System. Issue 1 (7th May 2018) - Convery, Alan; Lundberg, Thomas Carl
Abstract: Although there has been extensive research on electoral system choice at the national level, we know relatively little about the dynamics of deciding the rules of the game for sub-state institutions. This article examines the factors that influenced the choice of a proportional electoral system for the new Scottish Parliament in 1999. Through the use of archival sources and interviews with key participants, we challenge the conventional rational choice explanation for the adoption of the mixed-member proportional (MMP) system. Although rational considerations on the part of the Labour Party were involved in the choice of MMP, our findings suggest that, as at the national level, theories of electoral system choice need to consider normative values as well.